Aplikasi Mobile Periklanan Digiprom Berbasis Android - Muhammad Hafiz Taruligani Sihite; Ardiansyah; Rizky Prabowo; Febi Eka Febriansyah (Jurnal Pepadun, 2022)
Digiprom is a startup that provides ad serving services. These advertisements will later be shown in public places, such as supermarkets, cafes, malls, and others. The problem faced by Digiprom is that there is no information technology to help interact between Digiprom and its clients (businessman). The interactions in question are such as registration as a client, the process of making a contract between the client and Digiprom, the process of monitoring the contract that has been made and the delivery of other information about Digiprom. To solve this problem, an Android-based mobile application will be developed to help Digiprom interact with its clients. This research focuses on the development side of the Android application, while the server side is not included in this study. The development of this application will use the Waterfall method and tested using black box testing and user acceptance testing. The system design is described using three UML diagrams, namely use case diagrams, activity diagrams and class diagrams. Program code written using Kotlin language with MVVM architecture (Model, View, ViewModel). There are three main objects in this system, namely users (businessman/clients), ads (advertisements) and location (advertising locations). Each object will have its own repository. The repository has three data sources, namely network (server), Room Database, and Data Store. The use of MVVM architecture facilitates the development and maintenance process, because if there is a change in the data structure of an object, it will not affect the data structure of other objects. The results of this research (Android application) will be uploaded to the Google Play Store under the name Digiprom.